Intrasaccular therapy in wide-neck intracranial aneurysms: a narrative review - Zhuo, Kaiquan; Wu, Hongxia; Gou, Zhongji; Zhang, Changwei (Frontiers in Neurology, 2025)
The treatment of wide-neck intracranial aneurysms (WNIAs) is a challenge in interventional therapy. Intrasaccular therapy, including intrasaccular flow disruption or formation of a neck bridge within the saccular, has been extensively used recently. The Medina® Embolisation Device, Luna™ Aneurysm Embolisation System, Artisse™ Aneurysm Embolisation System, Contour Neurovascular System™, Neqstent™ Coil Assisted Flow Diverter, Woven EndoBridge (WEB) device, Nautilus™ Intrasaccular System, and Trenza Embolization Device™ have obtained Conformité Européene Mark certification. However, only WEB devices have been approved by the US Food and Drug Administration. The SEAL™ Endovascular Embolization System is approved for sale only in New Zealand. Angiographic results post-procedure and in the follow-up are the main indices used to measure the efficacy of intrasaccular therapy. Complications include ischaemia, thromboembolism, and related haemorrhage. This review summarizes and discusses the efficacy and safety of intrasaccular devices in treating WNIAs. Despite this, complete and satisfactory occlusions are accomplished in most cases of intrasaccular therapy for WNIAs, and the associated complications are typically regarded as acceptable. However, it is important to note that the occlusion rate with intrasaccular therapy is generally lower than that achieved through surgical clipping. Long-term follow-up of intrasaccular therapy and recurrence and retreatment of WNIAs is limited.